CRISPR/Cas Technology: Revolutionize the Germ Cell Editing - Ritika,; Pal, Hanshika; Shavi,; Lalaji Selokar, Naresh; Kumar Singh, Manoj (The Indian Journal of Animal Reproduction, 2025)
CRISPR-Cas9-based editing in germ cells like PGCs, spermatogonial stem cells, oocytes, and early embryos can poten tially correct heritable genetic disorders, preventing their transmission to future generations. Additionally, CRISPR based gene editing in germ cells can enhance fertility by repairing mutations linked to infertility. Despite its potential,  germline editing presents significant challenges like off-target effects, unintended mutations, and mosaicism, raising  concerns about safety and long-term consequences. Advances in base and prime editing techniques aim to improve  precision and reduce unwanted mutations. Ongoing research focuses on enhancing editing efficiency, understanding the  implications of heritable changes, and developing ethical frameworks to govern its use. This review emphasizes genome  editing in germ cells to revolutionize animal breeding, ensuring more sustainable agricultural practices and long-term  benefits for society. As the field progresses, balancing scientific innovation with ethical responsibility will be crucial in  determining the future of CRISPR-based germline editing.
Keywords: CRISPR/Cas; Germ cell; Genome editing.